2009
DOI: 10.1111/j.1600-0838.2009.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral ankle sprain alters postural control in bipedal stance - part 1: restoration over the 30 days following the injury

Abstract: The time evolution of the postural behavior of 23 lateral ankle sprain patients (degrees I and II) were evaluated 14 h and 10 and 30 days on average after their injury and compared with those of 30 age-matched healthy individuals. The patients were tested with separate measurements of the reaction forces under each limb to highlight the possible compensatory mechanisms between the sound and the injured legs. Their postural behavior in bipedal stance was characterised by a weight-bearing asymmetry with more wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…15,16 Findings of these studies, however, have been inconsistent. Genthon et al 9 observed postural-stabilization asymmetry during bipedal stance, but Akbari et al 10 reported contrasting results, finding no postural-control asymmetries after an acute ankle sprain. Researchers 13,17 have also reported contrasting findings of postural-control impairments during single-legged balance after an acute ankle sprain.…”
mentioning
confidence: 99%
“…15,16 Findings of these studies, however, have been inconsistent. Genthon et al 9 observed postural-stabilization asymmetry during bipedal stance, but Akbari et al 10 reported contrasting results, finding no postural-control asymmetries after an acute ankle sprain. Researchers 13,17 have also reported contrasting findings of postural-control impairments during single-legged balance after an acute ankle sprain.…”
mentioning
confidence: 99%
“…In this train of thoughts, orientation refers to the body positioning relative to the feet while stabilization refers to the dynamic processes involved in the upright satnce maintenance. With this approach, the strategies and compensatory mechanisms between the two legs used for controlling upright quiet stance can be better understood (Genthon et al, 2008;Rougier and Bergeau, 2009;Genthon et al, 2010). In addition, a dissociation of the complex CP displacements into two basic components, the vertically projected center-of-gravity (CG v ) and the difference between CP and CG v (CP-CG v ), brings additional insights for describing the postural control mechanisms (Winter et al, 1996;Rougier and Caron, 2000).…”
mentioning
confidence: 99%
“…We found no studies in which researchers investigated the effects of pain on the residual impairments of CAI. Given that pain is known to affect functional activity, 11,41 we could hypothesize that participants with CAI who have pain may show differences in various functional performance measures compared with participants who do not have pain. Hass et al 42 demonstrated that chronic peripheral joint injury (ie, CAI) negatively altered the supraspinal aspects of motor control.…”
Section: Discussionmentioning
confidence: 99%